Dual-function engineering to construct ultra-stable anodes for potassium-ion hybrid capacitors: N, O-doped porous carbon spheres. (March 2022) - Dou, Shuming; Xu, Jie; Yang, Chao; Liu, Wei-Di; Manke, Ingo; Zhou, Wei; Peng, Xin; Sun, Congli; Zhao, Kangning; Yan, Zhenhua; Xu, Yunhua; Yuan, Qunhui; et al.
Abstract: Heteroatom doping engineering is deemed to be an adoptable strategy to boost the potassium (K) storage performance of carbonaceous materials. The inevitable issue for this strategy lies in the huge volume expansion originated from the large radius of K + . In this study, N/O co-doped porous carbon spheres (PCSs) with high-content –CO are fabricated by a reliable and simple annealing route. Through dual-function engineering for heteroatom doping and pore constructing, the PCSs shows outstanding K + -storage performance with remarkable reversible capacity (389.8 mAh g −1 at 0.1 A g −1 ), superior rate capability (201.7 mAh g −1 at 1 A g −1 ), and unprecedented ultralong-term cycling stability (107 mA h g −1 at 5 A g −1 after 40, 000 cycles with 0.00038% decay per cycle). In-situ Raman analysis uncovers that the PCSs undergoes a reversible adsorption-intercalation hybrid K + -storage mechanism. Specifically, density functional theory calculations and in-situ transmission electron microscopy observations elucidate the possible origins of the high reversible capacity and superb cycling stability by disentangling the synergistic effect of dual-function engineering. The PCSs can be used as the anode for potassium-ion hybrid capacitors (PIHCs) to deliver a high energy/power density. This work opens a new avenue to construct carbonaceous electrode candidates for high-performance PIHCs. Graphical Abstract: N/O co-doped porous carbon spheres (PCSs) with abundant mesopore structure are fabricated. The dual-function engineering for heteroatom doping and pore constructing can relieve the volume expansion and endow rapid ionic/electronic transport kinetics. As prepared PCSs anode shows outstanding K + -storage performance with superior rate capability and unprecedented ultralong-term life over 40, 000 cycles at 5 A g −1 . ga1 Highlights: N/O doped porous carbon spheres (PCSs) were designed and prepared through a dual-function engineering strategy. The obtained PCSs anode showed an unprecedented ultralong-term cycling life of 40, 000 cycles. In-situ Raman analysis uncovered that the PCSs undergoes a reversible adsorption-intercalation hybrid K + -storage mechanism. DFT calculations and in-situ TEM analysis revealed that the possible origins of the superb cycling performance. The PCSs can be used as the anode for potassium-ion hybrid capacitors to deliver a high energy/power density.